Out-of-plane orientation of luminescent excitons in two-dimensional indium selenide - Mauro Brotons-Gisbert (Nature Portfolio, 2019)
Room temperature photoluminescence of most 2D van der Waals semiconductors originate from in-plane dipoles. Here, the authors report a combination of far-field photoluminescence measurements and ab-initio calculations to demonstrate that 2D-InSe flakes sustain luminescent excitons with an intrinsic out-of-plane orientation.